Penerapan Teknologi E-Money Untuk Pembayaran Di SPBU Berbasis Mikrokontroler - Anip Findra Yurfianto; Sumaryanto Sumaryanto; Sulartopo Sulartopo (STEKOM PRESS, 2020)
The Madukoro gas station is one of the gas stations in Semarang where the payment and refueling systems are still done manually. In general, the manual payment and filling system has many obstacles, resulting in long queues because the service is not fast and effective, also triggering the exchange of counterfeit money because payment uses cash. The application of e-money technology based on microcontrollers is made to make a payment system using electronic money instead of cash that is integrated with fuel filling, this system aims to reduce the long queues that occur and also prevent the amount of counterfeit money circulating at gas stations and make services more fast and easy. The method used in the design of this system is to use the method of Research and Development (R&D) theory from Borg and Gill, starting with gathering information by interviewing Madukoro gas station supervisors and field surveys then designing and developing systems to overcome the problems obtained in research. The system design uses a microcontroller as a data processor that will retrieve data from a database that was previously inputted from the VB.Net application and e-money reader and outputs to instruct the pump to remove fuel from the tank in accordance with the calibration of fuel output per second. As information on the rest of the fuel in the tangka, this tool uses the help of a load sensor that will be displayed on the LCD. In general, this system will make services faster and easier, thereby reducing the number of long queues, but also to avoid the circulation of counterfeit money in gas stations Madukoro, Semarang.